2006
DOI: 10.1016/j.jconhyd.2005.10.010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of silica on the degradation of organohalides in granular iron columns

Abstract: Dissolved silica species are naturally occurring, ubiquitous groundwater constituents with corrosioninhibiting properties. Their influence on the performance and longevity of iron-based permeable reactive barriers for treatment of organohalides was investigated through long-term column studies using Connelly iron as the reactive medium. Addition of dissolved silica (0.5 mM) to the column feed solution led to a reduction in iron reactivity of 65% for trichloroethylene (TCE), 74% for 1,1,2-trichloroethane (1,1,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Despite the smaller amount of ZVI present in the mixture, the performance of this material and of pure ZVI at the same sampling port (3 cm) are comparable. It is interesting to note that the poorest performance was obtained using pumiceeZVI in series, probably since the presence of pumice upstream of the ZVI results in dissolution of small quantities of silica that reduce the performance of the iron (Kohn and Roberts, 2006). Moreover, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the smaller amount of ZVI present in the mixture, the performance of this material and of pure ZVI at the same sampling port (3 cm) are comparable. It is interesting to note that the poorest performance was obtained using pumiceeZVI in series, probably since the presence of pumice upstream of the ZVI results in dissolution of small quantities of silica that reduce the performance of the iron (Kohn and Roberts, 2006). Moreover, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although some researchers argue that dissolved silica promotes Fe 0 corrosion reaction by releasing protons in the solution through interaction with iron oxyhydroxide surface [45,46], recent studies have revealed its inhibitory effect on zero-valent iron reactivity over time [42,43]. In this study, three main distinct regions are observed by using SEM on polished sections of reacted iron-sand grains (Fig.…”
Section: Effect Of Sandmentioning
confidence: 80%
“…The decrease in iron reactivity could be also explained by the tendency of silica to serve either as an anodic corrosion inhibitor that prevents iron from releasing electrons to the metal contaminants or as chemical converter that changes the types of iron (hydr)oxide phases that may be formed. A previous iron-sand column study conducted for the treatment of organohalides showed that the inhibitory effect of silica sand is not only dependent on the concentration of dissolved silica species in the feed solution, but also on the type of iron used in the reactive matrix [42].…”
Section: Effect Of Sandmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the role that silica plays in reduced iron reactivity may also be compound-specific (Kohn and Lynn Roberts, 2006).…”
Section: Other Sources Of Uncertainty In the Long Term Prediction Andmentioning
confidence: 99%